P1169Cardiac resynchronization theraphy. Long term benefit. (18th June 2020) - Galizio, N; Peltzer, M; Tronconi, A; Carnero, G; Mysuta, M; Bozza, A; Gavilan, L; Labin, B; Gonzalez, J L
Abstract: Introduction: The benefit of cardiac resynchronization therapy (CRT) in patients (pts) with left ventricular dysfunction is mainly evaluated in multicenter studies with a follow up of 6, 12 or 24 months (m). Objectives: To describe the response of pts implanted with a CRT-D/P, from a single center prospective registry, at 12, 24, 36 and 48 m. Methods: Between june 2009 and june 2018, 381 pts implanted with CRT-D/P were followed at 12, 24, 36 and 48 m. Indications were performed according to international guidelines. Primary prevention: 335 pts (88%). The A-V and V-V delay were programmed according the results of Cardiac Doppler after implantation and when it was necesary. All pts had an out patient control and 10% remote monitoring control. The pts were considered Responders: decrease ≥ 1 FC NYHA or increase LVEF ≥ 5% (absolute), Super-Responders: increase LVEF ≥ 10% (absolute) and with LVEF normalization: LVEF ≥ 50%. Baseline characteristics: Age 64 ± 11 years, men 268 p (70%), ischemic cardiomyopathy 144 pts (38%), nonischemic cardiomyopathy 237 (62%), FC II-III NYHA 341 p (90%), LBBB 246 p (72%), mean QRSd 165 ± 27ms, mean LVDD 68 ± 10mm, mean LVSD 56 ± 12mm, and mean LVEF 24 ± 9%. Pts were on β-blockers (93%), ACEi/ARBs (90%), mineral receptor blockers (83%) and diuretics (73%). Results: Responders: 227/276 pts (82%) at 12 m, 184/224 pts (82%) at 24 m, 141/180 p (78%) at 36 m and 112/137 (82%) at 48 m. Super-Responders: 92/186 pts (49%) at 12 m, 92/172 pts (53%) at 24 m, 71/128 (55%) at 36 m and 66/116 (57%) at 48 m. LVEF normalization: 22/186 pts (12%) at 12 m, 31/172 pts (18%) at 24 m, 24/128 pts (19%) at 36 m and 23/116 pts (20%) at 48 m. Conclusion: In our study population, pts with CRT-D/P implanted according an appropriate indication, programming and follow up, with in-office and/or remote monitoring control, showed an elevated percentage of Responders, Super-Responders and LVEF normalization. The benefit was sustained or even incresed over time.